Grammar-Semantic Structure of Sentences of Causal Constructions in Korean language - Shokhsanam AKRAMOVA (Periodica Journal, 2022)
This article reveals the semantics of the structure of sentences, inwhich constructions are presented that express a causal relationship.This is due to the fact that there are a lot of such constructions inKorean language. However, in the research area of linguistics ofKorean language there is no clear system for distinguishing betweencases of using one or another construction. This complicates the taskof understanding, interpreting, translating, teaching the Koreanlanguage
Keywords: Grammar-Semantic Structure, Causal Constructions in Korean, a causal relationship